68Ga-NOTA-RM26 PET/CT in the evaluation of glioma: a pilot prospective study - Yilin Li; Rongxi Wang; Jingci Chen; Zhaohui Zhu; Yu Wang; Wenbin Ma (EJNMMI Research)
Abstract Background Gliomas are the most common malignant primary tumors of the central nervous system. There is an urgent need for new convenient, targeted and specific imaging agents for gliomas. This study aimed to firstly evaluate the feasibility of 68Ga-NOTA-RM26 PET/CT imaging in glioma and analyze the relationship between the imaging characteristics and glioma grade, classification and molecular alterations. Results Twenty-two patients were confirmed as glioma by surgery or biopsy. All patients exhibited 68Ga-NOTA-RM26 uptake. SUVmax was chosen as the imaging marker for analysis. For all glioma patients, there were significant differences between grades (P = 0.047). For primary gliomas, SUVmax had good discrimination for both tumor classifications (P = 0.045) and grades (P = 0.03). There was a positive correlation (P < 0.01) between GRPR expression level and SUVmax. P53 mutations caused significant differences in SUVmax (P = 0.03). Conclusions This study is the first application of 68Ga-NOTA-RM26 in glioma patients and confirmed the safety and efficacy in glioma patients. 68Ga-NOTA-RM26 PET/CT has potential value in tumor grade, classification, and molecular alterations. Trial registration ClinicalTrials.gov: NCT06412952. Registered 26 April 2024, https://clinicaltrials.gov/study/NCT06412952